Linkage analysis of a DNA polymorphism proximal to the Duchenne and Becker muscular dystrophy loci on the short arm of the X chromosome. - Brown, C S (1985)
The inheritance of a restriction fragment length polymorphism (RFLP) detected by a cloned DNA sequence (p754) from the short arm of the X chromosome has been studied in 14 Duchenne muscular dystrophy kindreds and six Becker muscular dystrophy kindreds. The linkage data obtained suggest that both the DMD and BMD loci are located in the same region (p21) on the short arm of the X chromosome at a distance of about 15 to 20 cM from the 754 locus. Data from families informative for both the p754 and L1.28 polymorphisms suggest that p754 is closer to the disease loci than is L1.28.